Noncompliance to Treatment and Its Associated Factors among Patients with Diabetes Mellitus in Karachi - Sannia Perwaiz Iqbal; Rubia Farid; Ainan Arshad (Shalamar Medical & Dental College, Lahore, Pakistan, 2023)
Background: Noncompliance to treatment is a widespread problem globally, particularly among people with chronic conditions like diabetes mellitus. Objective: We aimed to assess the frequency of treatment noncompliance and its associated factors among patients with type 2 diabetes. Methods: The study was conducted at the family medicine outpatient clinics at the Aga Khan Hospital during one month from 1st to 30th December, 2019. Using a cross-sectional design, we recruited 151 patients with type 2 diabetes who willingly agreed to participate in the research. We employed a pre-approved, self-administered, and structured questionnaire to gather data on demographics, clinical features, and treatment compliance among patients.   Results: There were 77 female and 74 male participants. The average age of the participants was 54.7±11.5 years. Among the 151 individuals in the study, 112 were noncompliant with their prescribed treatment. There was a significant association between treatment non-compliance and lower monthly income (p=0.039), participant's age (p=0.020), and duration of the disease exceeding 5 years (p<0.001). The group of patients with noncompliance also had a higher risk of diabetic foot (p = 0.002) and retinopathy (p = 0.009). When asked about their reasons for noncompliance, participants cited drug side effects (91%), forgetfulness to take medications (81%), and complexity of drug therapy (66%). Conclusion: Our findings revealed a notable prevalence of noncompliance among participants, which was associated with an elevated risk of complications. The Older age and disease duration for longer than 5 years were factors associated the most with noncompliance. Such interventions could significantly reduce the likelihood of developing diabetes-related complications.